2020
DOI: 10.3389/fmicb.2020.01618
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Genetically Related Clostridium Difficile Strains at a Single Hemato-Oncology Ward Over 10 Years

Abstract: Aims: Clostridium difficile ( C. difficile ) infection (CDI) is the main cause of healthcare-associated infectious diarrhea. We used whole-genome sequencing (WGS) to measure the prevalence and genetic variability of C. difficile at a single hemato-oncology ward over a 10 year period. Methods: Between 2008 and 2018, 2077 stool samples were obtained from diarrheal patients hospitalized at the Department of Lymphoma; of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…As reported recently [70], between 2008 and 2018, all patients hospitalized at the Department of Lymphoma with healthcare-associated diarrhea (defined as ≥3 stools within a 24-h period arising over the third day after hospital admission) underwent testing at the Department of Clinical Microbiology to detect pathogenic C. difficile toxins A and B. Tests were performed using the C. difficile TOX A/B kit (TechLab).…”
Section: Methodsmentioning
confidence: 99%
“…As reported recently [70], between 2008 and 2018, all patients hospitalized at the Department of Lymphoma with healthcare-associated diarrhea (defined as ≥3 stools within a 24-h period arising over the third day after hospital admission) underwent testing at the Department of Clinical Microbiology to detect pathogenic C. difficile toxins A and B. Tests were performed using the C. difficile TOX A/B kit (TechLab).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, a study by Walker et al analysed 41 recurrent episodes in cancer patients using WGS and found that 29% of these episodes were caused by a different strain, indicating reinfection. However, when recurrence occurred within the first 2 months after the initial CDI, it was always caused by the original strain [47]. The study also revealed a high prevalence of genetically related strains, suggesting possible nosocomial transmission, although this aspect was not specifically addressed.…”
Section: Andandmentioning
confidence: 86%